2019
DOI: 10.18326/rgt.v12i2.126-156
|View full text |Cite
|
Sign up to set email alerts
|

A Child Language Acquisition in Indonesian and English Language: A Longitudinal case study

Abstract: Learning a dual language at the same time during early childhood has caused the wrong perception. Its false perception makes the parents delay the start of learning a second /foreign language. Therefore, This study aims at analyzing the first and second language acquisition of a child in the Indonesian Language and English. The issues concentrated on the spoken utterances in Indonesian and English and its affecting factors. The research adopted a qualitative approach by using a case study, as the unit analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Likewise, socialeconomy status is viewed as factor as source of individual variation in some child SLA research as well as quality and context of second language input. The almost similar insight has been reported by Fitriani (2019). Based on her research, it was concluded that the linguistic input, language acquisition devices, imitation, environment and immediate family are factors affecting the child L2 spoken utterances.…”
Section: The Psycholinguistic Paradigmsupporting
confidence: 74%
See 2 more Smart Citations
“…Likewise, socialeconomy status is viewed as factor as source of individual variation in some child SLA research as well as quality and context of second language input. The almost similar insight has been reported by Fitriani (2019). Based on her research, it was concluded that the linguistic input, language acquisition devices, imitation, environment and immediate family are factors affecting the child L2 spoken utterances.…”
Section: The Psycholinguistic Paradigmsupporting
confidence: 74%
“…Meanwhile, the term language acquisition can be defined as the learning on structures or rules. It refers to the grammar construction, the phonological elements of sound patters, syntactical structures of language and others; while, the term 'development' is commonly characterized by the use of the acquired language and its element (rules, structure, and meaning) in various language contexts (Wray & Bloomer, 2006in Fitriani, 2019.…”
Section: Child Second Language Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the vocal phonemes are: / i, e, a, ə, o, u. For example, in bahasa Indonesia, /r/ and /l/ are different because /paru/ and /palu/ have different meaning (Fitriani, 2019). So, every phoneme of any languages has its own form.…”
Section: Phonemesmentioning
confidence: 99%
“…MLU has been divided into MLU-m (morpheme) and MLU-w (word), with the use of MLU-w, claimed as a more reliable measure for calculating the length of utterance as well as a more sensitive one to the child's language complexity (Nóro & Mota, 2019). socioeconomic background, i.e., middle-high SES (Fitriani, 2019). One study reported multiple cases with no SES context mentioned (Marsis & Annisa, 2018).…”
Section: Introductionmentioning
confidence: 99%